Caffeine Improves Heart Rate Without Improving Sepsis Survival. Issue 2 (August 2015) - Bauzá, Gustavo; Remick, Daniel
Abstract : ABSTRACT: Introduction : Caffeine is consumed on a daily basis for its nervous system stimulant properties and is a global adenosine receptor antagonist. Because adenosine receptors have been found to play a major role in regulating the immune response to a septic insult, we investigated if caffeine consumption prior to a septic insult would alter immunological and physiological responses, as well as survival.Methods : Two separate experimental designs were used, both using outbred female ICR mice. In the first experiment, mice were administered 20 mg/kg of caffeine (equal to 2–3 cups of coffee for a human) or normal saline intraperitoneally at the time of cecal ligation and puncture (CLP). Immunological parameters including cytokines and local cell recruitment were measured. In the second experiment, caffeine (10 mg/kg per hour) was delivered continuously for 24 h via a subcutaneous infusion pump placed the day prior to CLP, and hemodynamic parameters were examined. In both experiments, survival was followed for 5 days.Results : A single dose of caffeine at the initiation of sepsis did not alter survival. This single dose of caffeine did significantly increase in plasma levels of the chemokine KC 6 h after the onset of sepsis compared with septic mice given normal saline. There were no changes in interleukin 6 (IL-6) or IL-10 levels in the caffeine groups. Peritoneal lavages performed 24 h after CLP showed no difference in the levels of IL-6, tumor necrosis factor, KC, macrophage inflammatory protein 1, IL-10, or the IL-1 receptor antagonist between caffeine- and normal saline–treated mice. In addition, the lavages yielded similar numbers of cells (4.1 × 10 6 vehicle vs. 6.9 × 10 6 caffeine) and bacterial colony-forming units (CFUs, 4.1 million CFUs vehicle vs. 2.8 million CFUs caffeine). In the infusion group, caffeine also did not alter survival. However, caffeine infusion did increase the heart rate prior to CLP and prevented the decline in heart rate after CLP.Conclusion : Caffeine increased the heart rate in mice but does not impact cytokine responses or survival during the acute phase of a polymicrobial sepsis challenge. These data indicate that patients consuming caffeine will not be at risk for increased sepsis mortality.